Multilingualism of a Southern Estonian – comparison of Estonian, Võru and Finnish narratives - Liina Tammekänd (Eesti Rakenduslingvistika Ühingu Aastaraamat, 2013)
The main subjects of the present case study are structural analysis of multilingual autobiographical narratives, and multilingualism and emotions. The respondent told an emotional story from her childhood in Estonian, in the Võru dialect and in Finnish. The author recorded, transcribed and analysed the three narratives keeping in mind four research questions: Do the narratives differ from each other structurally and thematically? Is the respondent’s L1 emotionally closer to her? Does the respondent present different selves and emotional repertoire in her different languages? The narratives are structurally similar but thematically different. Because of the emotional vocabulary and themes in the Võru narrative, the Võru dialect seems emotionally closer to the respondent than the other two languages. No extensive conclusions could be made regarding the different selves. The speaker uses a different emotional repertoire in Finnish compared with the other languages. DOI: http://dx.doi.org/10.5128/ERYa9.19